2021
DOI: 10.1111/dth.15248
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical factors as possible predictors of response to omalizumab and relapse after treatment discontinuation in chronic spontaneous urticaria

Abstract: Omalizumab is a monoclonal anti‐IgE antibody which is effective in chronic spontaneous urticaria (CSU), although clinical response appears to be variable in the real‐life setting. The aim of this study was to evaluate whether the response of CSU to omalizumab and disease relapse are associated with individual and/or clinical characteristics of patients. We retrospectively evaluated the clinical records of 124 patients treated with omalizumab for moderate to severe CSU refractory to antihistamines. Disease acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our results are in line with the results of Foti C et al [7], a two-center study that also reported that atopy had no influence in omalizumab response in CSU patients. In contrast, Cakmak ME reported that atopic CSU patients are better responders to omalizumab [5].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in line with the results of Foti C et al [7], a two-center study that also reported that atopy had no influence in omalizumab response in CSU patients. In contrast, Cakmak ME reported that atopic CSU patients are better responders to omalizumab [5].…”
Section: Discussionsupporting
confidence: 93%
“…We compared our results with previous studies that have also explored the possible influence of atopy on omalizumab response in CSU [5‒7]. It is known that some techniques of skin prick testing may be more likely to trigger dermographism.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With respect to sex and recurrence, there is no correlation with age, body mass index, peripheral eosinophil counts, total IgE levels, D-dimer levels, plasma prothrombine levels or C-reactive protein, and no sex differences in tolerability or safety are observed [ 113 ]. In contrast, other authors found no significant differences in sex, age and thyroid autoimmunity between responders and non-responders in CSU patients treated with omalizumab [ 114 ]. The pathogenic role played by female hormones in CU and allergic asthma, both of which exhibit a good response to omalizumab and high prevalence in females, highlights the possible action of omalizumab directly on sex hormones, or indirectly on the downstream mechanisms they mediate.…”
Section: Sex Difference In Omalizumab Therapymentioning
confidence: 94%
“…In some studies, but not others, higher rates of relapse were linked to long pre-treatment disease duration, being female, fast response to treatment, or high baseline disease activity [36][37][38]. While these markers may predict relapse on a group level, they are not useful for the prediction of relapse or for guiding stepping-down decisions for individual patients.…”
Section: The Role Of Spontaneous Remission In the Discontinuation Of ...mentioning
confidence: 99%